2008
DOI: 10.1182/blood-2008-04-152520
|View full text |Cite
|
Sign up to set email alerts
|

Prion diseases are efficiently transmitted by blood transfusion in sheep

Abstract: The emergence of variant CreutzfeldJakob disease, following on from the bovine spongiform encephalopathy (BSE) epidemic, led to concerns about the potential risk of iatrogenic transmission of disease by blood transfusion and the introduction of costly control measures to protect blood supplies. We previously reported preliminary data demonstrating the transmission of BSE and natural scrapie by blood transfusion in sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
138
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 35 publications
10
138
3
1
Order By: Relevance
“…10 Transmission of TSE via blood was also observed in transfusion experiments performed using sheep that were infected with scrapie, indicating that not only vCJD but also other form of TSE could be transmitted via blood. 10,11 The infectivity titer of TSE in the blood was found to be 1-2 log10 LD50/ml, which was extremely low compared to that found in the brains of infected animals. 10 This indicates that only a minimum amount of the PrPres is present in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…10 Transmission of TSE via blood was also observed in transfusion experiments performed using sheep that were infected with scrapie, indicating that not only vCJD but also other form of TSE could be transmitted via blood. 10,11 The infectivity titer of TSE in the blood was found to be 1-2 log10 LD50/ml, which was extremely low compared to that found in the brains of infected animals. 10 This indicates that only a minimum amount of the PrPres is present in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism underlying the transmission of prion infectivity from ewe to lamb remains poorly understood. Since it has been demonstrated that prion infectivity is harbored in the blood of sheep with scrapie, 25 vertical transmission could simply result from the large accumulation of blood in the placenta. Indeed, PrP Sc has been observed at the fetal-maternal interface of infected sheep.…”
Section: Discussionmentioning
confidence: 99%
“…6,16,17 HBV vaccination was advised a total of 188 times, and administration of HBIg was advised only 41 times. This is in accordance with our other studies, in which a reduction in HBIg administration was calculated after the introduction of the new Dutch national guidelines.…”
Section: Discussionmentioning
confidence: 99%